The Selective Phosphoinoside-3-Kinase p110δ Inhibitor IPI-3063 Potently Suppresses B Cell Survival, Proliferation, and Differentiation - Chiu, Honyin; Mallya, Sharmila; Nguyen, Phuongthao; Mai, Annie; Jackson, Leandra V.; Winkler, David G.; DiNitto, Jonathan P.; Brophy, Erin E.; McGovern, Karen; Kutok, Jeffery L.; Fruman, David A. (Frontiers in Immunology, 2017)
The class I PI3Ks are important enzymes that relay signals from cell surface receptors to downstream mediators driving cellular functions. Elevated PI3K signaling is found in B cell malignancies and lymphocytes of patients with autoimmune disease. The p110δ catalytic isoform of PI3K is a rational target since it is critical for B lymphocyte development, survival, activation, and differentiation. In addition, activating mutations in PIK3CD encoding p110δ cause a human immunodeficiency known as activated PI3K delta syndrome (APDS). Currently idelalisib is the only selective p110δ inhibitor that has been FDA approved to treat certain B cell malignancies. p110δ inhibitors can suppress autoantibody production in mouse models, but limited clinical trials in human autoimmunity have been performed with PI3K inhibitors to date. Thus, there is a need for additional tools to understand the effect of pharmacological inhibition of PI3K isoforms in lymphocytes. In this study, we tested the effects of a potent and selective p110δ inhibitor, IPI-3063, in assays of B cell function. We found that IPI-3063 potently reduced mouse B cell proliferation, survival, and plasmablast differentiation while increasing antibody class switching to IgG1, almost to the same degree as a pan-PI3K inhibitor. Similarly, IPI-3063 potently inhibited human B cell proliferation in vitro. The p110γ isoform has partially overlapping roles with p110δ in B cell development but little is known about its role in B cell function. We found that the p110γ inhibitor AS-252424 had no significant impact on B cell responses. A novel dual p110δ/γ inhibitor, IPI-443, had comparable effects to p110δ inhibition alone. These findings show that p110δ is the dominant isoform mediating B cell responses and establish that IPI-3063 is a highly potent molecule useful for studying p110δ function in immune cells.